UNDERSTANDING THE IMPACT OF PURCHASE INTENTION AMONG GEN Z ON PRODUCT REVIEWS ON ELECTRONIC PRODUCTS - Ghazlan Atqiya Firmansya; Beatrix Benedicta Harlan; Tri Wismiarsi (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
The research investigates the relationship between product reviews for electronic devices and purchase intention among Indonesian Gen Z customers. It explores how review valence, review quantity, brand trust, and product familiarity influence purchase intention with a focus on perceived risk, and brand image. This study used quantitative approach as a method of research. It used a survey to collect data, and the survey was distributed to 103 valid Gen Z respondents who had previously purchased electronic devices online. The data were analyzed using statistical analysis to test the hypotheses. The research results indicate that product familiarity, review quantity, review valence, and brand trust are among the significant variables that influenced electronic product purchase intentions. In order to enhance consumer trust and purchase likelihood, e-commerce platforms and businesses should focus on boosting both the quantity and quality of online reviews. Strategies such as rewarding user reviews and responding quickly to negative feedback are being suggested to boost company image and drive sales among Generation